(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
Chrome tanning is a versatile tanning system, but the pollution problems of chromium due to inadequacy of treatment systems and possible formation of Cr(VI), a carcinogen, have led to search for an ecofriendly and viable alternative tanning system. The present investigation focuses on the development of a novel, high performance and thermally stable aldehyde tannage system to produce chrome free leather by cross linking the NH2 groups of collagen with glutaraldehyde (CHO-CH2-CH2-CH2-CHO). After as usual soaking, liming, deliming, bating and pickling operations the pickle pelts were tanned with glutaraldehyde and other syntans. This developed chrome free tanning process produce crust leathers exhibiting thermal stability >85Â°C and reducing the TDS value with 0% emission of Cr-salt in tannery discharge. Key words: Eco friendly tanning system, Chrome free leather, Crust leathers Â doi: 10.3329/bjsir.v43i4.2246 Â Bangladesh J. Sci. Ind. Res. 43(4), 553-558, 2008